2015
DOI: 10.2514/1.c032864
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Summary of the Second AIAA High-Lift Prediction Workshop

Abstract: The second AIAA CFD High-Lift Prediction Workshop was held in San Diego, California, in June 2013. The goals of the workshop continued in the tradition of the first high-lift workshop: to assess the numerical prediction capability of current-generation computational fluid dynamics (CFD) technology for swept, medium/high-aspect-ratio wings in landing/takeoff (high-lift) configurations. This workshop analyzed the flow over the DLR-F11 model in landing configuration at two different Reynolds numbers. Twenty-six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Some of the TMR website cases were used as verification exercises at two recent validation workshops: DPW-5 9 and HiLiftPW-2. 10 In the DPW-5 workshop, the 2-D flat plate and 2-D bump were used as verification tests. The use of grid convergence studies was shown to be crucial, as expected.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the TMR website cases were used as verification exercises at two recent validation workshops: DPW-5 9 and HiLiftPW-2. 10 In the DPW-5 workshop, the 2-D flat plate and 2-D bump were used as verification tests. The use of grid convergence studies was shown to be crucial, as expected.…”
Section: Introductionmentioning
confidence: 99%
“…The same mesh was used for Case 2a at the lower Reynolds number. Additional details about the gridding guidelines and specific grids are not provided here, but documentation can be found in [2,3] or on the HiLiftPW-2 website. ** A comparison of grid sizes is shown in Table 2 for the workshop-supplied grids.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six participants submitted a total of 48 data sets of CFD results on a variety on grid systems (both structured and unstructured). An overview and summary of the workshop is given by Rumsey and Slotnick [2]. Many workshop participants have summarized individual submissions and provided additional analysis and computations [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…CFD methods, however, still suffer due to the inability to deal with highly separated flows that are typical for a wing in the post-stall regime. 51 In addition, building an accurate set of lookup tables for flight simulation would take prohibitively long even using Reynolds-Averaged Navier Stokes (RANS) CFD simulations. For this study, the authors did not use CFD in the aerodynamic modeling.…”
Section: A Airfoil Modelmentioning
confidence: 99%